1990
DOI: 10.1007/bf00154372
|View full text |Cite
|
Sign up to set email alerts
|

Periodicities of solar irradiance and solar activity indices, I

Abstract: Using a standard FFT time series analysis, our results show an 8-11 months periodicity in the solar total and UV irradiances, 10.7 cm radio flux, Ca-K plage index, and sunspot blocking function. The physical origin of this period is not known, but the evidence in the results exclude the possibility that the observed period is a harmonic due to the FFT transform or detrending. Periods at 150-157 and 51 days are found in those solar data which are related to strong magnetic fields. The 51-day period is the domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
80
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(91 citation statements)
references
References 35 publications
11
80
0
Order By: Relevance
“…However, the 27 day periodicity refers to the solar rotation, which is most common due to all the active centers or exciter hotspot being very close to the equator, particularly during the declining phase of the solar cycle. Our results endorse the earlier conclusion by Pap et al (1990) that this periodicity arises because active regions and their magnetic field are better organized and are long-lived during the maximum and declining portions of the solar cycle compared with the rising portion. Our discovery of a 31 day periodicity, though not prominent, in all the energy bands suggests that many sunspot regions did not approach close to the equator during the declining phase of cycle 23.…”
Section: Discussionsupporting
confidence: 92%
“…However, the 27 day periodicity refers to the solar rotation, which is most common due to all the active centers or exciter hotspot being very close to the equator, particularly during the declining phase of the solar cycle. Our results endorse the earlier conclusion by Pap et al (1990) that this periodicity arises because active regions and their magnetic field are better organized and are long-lived during the maximum and declining portions of the solar cycle compared with the rising portion. Our discovery of a 31 day periodicity, though not prominent, in all the energy bands suggests that many sunspot regions did not approach close to the equator during the declining phase of cycle 23.…”
Section: Discussionsupporting
confidence: 92%
“…Except for 33.5 and 85 day periodicities, all the periodicities have periods very close to integral multiples of 25.5 days. In addition, analyses of daily sunspot areas have detected periodicities at 51 days (Pap et al 1990) and 78 days (Bai & Sturrock 1991). Second, except for the 34 day periodicity, all the periodicities are visually recognizable in time profiles of flare rates smoothed with a 27 day moving window.…”
Section: Summary and Discussionmentioning
confidence: 94%
“…This periodicity was also detected from data of times earlier than cycle 19: cycle 2 (Ballester, Oliver, & Baudin 1999) and cycles 16-18 (Carbonell & Ballester 1992;Oliver et al 1998;Ballester et al 1999;Krivova & Solanki 2002), but not cycles 12-15 (Carbonell & Ballester 1992). In addition to the 154 day periodicity, Pap, Tobsika, & Bouwer (1990) discovered a 51 day periodicity in active sunspot areas (areas of growing sunspot groups) of cycle 21. Results of periodicity analyses of sunspot numbers generally agree with the results of sunspot area analyses (Lean & Brueckner 1989;Krivova & Solanki 2002), but Verma & Joshi (1987), for some reason, did not detect the 154 day periodicity from sunspot numbers of cycle 21.…”
Section: Introductionmentioning
confidence: 99%
“…Lean and Brueckner (1989) found it in the power spectrum of the sunspot-blocking function, in the 10.7-cm radio flux, the sunspot number, and in the plage-index daily data during three solar cycles (19 -21). Pap, Tobiska, and Bouwer (1990) showed that an 8 -11 month period existed in the total and UV irradiances (1980 and 1982 -1988, respectively), in the 10.7-cm radio flux (1947 -1989), the Ca K plage index (1970 -1987), the sunspot blocking function (1874 -1982), and the Mg II core-wing ratio (1978 -1986). Akioka et al (1987) detected it in areas and numbers of sunspot groups from 1969 to 1986.…”
Section: Introductionmentioning
confidence: 99%